LIFE CYCLE COST OF BIOMASS POWER PLANT - MONTE CARLO SIMULATION OF INVESTMENT - Odavić, Petrana; Zekić, Vladislav; Milić, Dragan (Economics of Agriculture, 2017)
Assessment of life cycle cost is considered as an important instrument for designing and evaluating success of every project. The aim of this work is to determine the precise impact of the investment costs and future operating and maintenance costs of CHP biomass plant. By using the Monte Carlo simulation are determined variations in the settings and the possible impact on the investment risk. The results show that the investment is justifed, thanks to the positive outcome of the net present value (NPV), internal rate of return (IRR) and the payback period. The greatest impact on the variability of annual profts have operating costs, which have the highest coefficient of variation of 6.44% and the largest share. Variability of net present value of 4% is acceptable, and the investment is considered as stable.